THE ANALYSIS OF GIVING REWARDS BY THE TEACHER IN LEARNING MATHEMATICS GRADE 5 STUDENTS OF SD NEGERI 184 PEKANBARU - Sri Yunengsih; Syahrilfuddin Syahrilfuddin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to find out and describe the rewards given by teachers in learning mathematics of fifth grade students of SD Negeri 184 Pekanbaru . This research was conducted in grade 5 SD Negeri 184 Pekanbaru on Jl. Putri Tujuh Pekanbaru. The activity was carried out in odd semester 2019/2020 which held on 11 November 2019 - 6 December 2019. The type of research was qualitative research. Based on the results of this study concluded that the provision of rewards by teachers in grade 5 SDN 184 Pekanbaru been implemented well in learning mathematics. These forms of rewards given in the form of verbal and non-verbal,  prize, and  value rewards. The impact of giving rewards given by teachers to students in learning mathematics has an impact on student motivation. Students are enthusiastic in participating in learning and students self-confidence is increasing.